1988
DOI: 10.1111/j.1365-2265.1988.tb00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Facilitates Ovulation Induction by Gonadotrophins

Abstract: The addition of biosynthetic human growth hormone (GH) to treatment with human menopausal gonadotrophin (hMG) significantly augmented the ovarian response in four patients treated for in-vivo and three patients treated for in-vitro fertilization who had previously been resistant to hMG. The amount, duration of treatment and daily effective dose of hMG were all reduced by growth hormone. This action of growth hormone offers a new approach to ovulation induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0
4

Year Published

1990
1990
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(95 citation statements)
references
References 7 publications
4
87
0
4
Order By: Relevance
“…Recently, we have demonstrated that the administration of exogenous growth hormone (GH) supplementation, in conjunction with standard ovarian stimulation regimens, resulted in significantly higher embryo implantation and clinical pregnancy rates compared with those not treated with GH (Yovich & Stanger 2010). These findings are supported by previous studies demonstrating the beneficial effect of GH in increasing the response of human ovary to gonadotrophins in poor-responder patients (Homburg et al 1988, Volpe et al 1989, Hazout et al 2009). The improvement in clinical outcomes was likely achieved via an improvement in oocyte developmental competence, rather than the result of an increased yield of oocytes or effects on the endometrium as the benefits continued to express in subsequent frozen embryo transfer cycles.…”
Section: Introductionsupporting
confidence: 77%
“…Recently, we have demonstrated that the administration of exogenous growth hormone (GH) supplementation, in conjunction with standard ovarian stimulation regimens, resulted in significantly higher embryo implantation and clinical pregnancy rates compared with those not treated with GH (Yovich & Stanger 2010). These findings are supported by previous studies demonstrating the beneficial effect of GH in increasing the response of human ovary to gonadotrophins in poor-responder patients (Homburg et al 1988, Volpe et al 1989, Hazout et al 2009). The improvement in clinical outcomes was likely achieved via an improvement in oocyte developmental competence, rather than the result of an increased yield of oocytes or effects on the endometrium as the benefits continued to express in subsequent frozen embryo transfer cycles.…”
Section: Introductionsupporting
confidence: 77%
“…One other option is administration of growth hormone (GH) to potentiate the effect of exogenous gonadotropins [3]. Growth hormone is reported to modulate the action of FSH on granulosa cells by up-regulating the local synthesis of insulin-like growth factor-I.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several studies have demonstrated that GH treatment increases ovary sensitivity to gonadotropin stimulation in infertile women with hyposensitive ovaries (12)(13)(14)(15)(16)(17)(18)(19). The effect of GH administration on gonadal function in men has been poorly investigated.…”
Section: Introductionmentioning
confidence: 99%